PELATIHAN KURSUS DASAR PERKOPERASIAN BAGI ANGGOTA KOPERASI KREDIT RUKUN KOTA PALEMBANG - Yohanes Susanto; Nelly Khairani Daulay (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Economic actors tend to be faced with intense competition. One of the economic actors in the cooperative movement, every aspect of the cooperative is an important thing that must be understood by every member of the joint so that it can be adequately developed; one of the credit cooperatives in the city of Palembang whose existence is running very well is a harmonious credit cooperative, with the number of members in 2020 as many as 12,555 people. One of the work programs in fostering its members is the provision of basic course materials for new members. This is the basis for the implementation of service, which aims to increase the knowledge and understanding of cooperative members so that they know their rights and obligations as members of harmonious credit cooperatives. The method used in this service is the lecture method directly to the trainees, and by providing material to cooperative members in the form of knowledge of the rights and obligations as members of cooperatives and the legal basis for managing cooperatives, then an evaluation is carried out after the provision of material is completed based on the review. The results of this service show significant differences in members' knowledge before and after training. This is following the set output by increasing and understanding cooperative members about their rights and obligations. It is hoped that by contributing to the Palembang City Cooperative Credit Cooperatives, they will be able to improve the welfare of these members and their families.--- Pelaku ekonomi  dihadapkan pada kompetisi yang sengit dalam persaingan global. salah satu pelaku ekonomi itu merupakan koperasi tiap pandangan dalam koperasi ialah perihal yang berarti yang wajib dipahami oleh setiap anggota koperasi agar dapat dikembangkan dengan baik, salah satu koperasi kredit di kota palembang yang eksistensinya  berjalan sangat baik adalah koperasi kredit rukun, dengan jumlah anggota  tahun 2020 sebanyak 12.555 orang dan salah satu program kerja dalam pembinaan anggotanya adalah pemberian materi kursus dasar bagi anggota baru. Perihal inilah yang jadi bawah penerapan dedikasi yang bermaksud buat meningkatkan pengetahuan dan pemahaman anggota koperasi agar mengetahui hak dan kewajiban sebagai anggota koperasi kredit rukun. Metode yang digunakan dalam pengabdian ini dengan metode ceramah dan  diskusi  secara langsung pada peserta pelatihan dan dengan memberi materi kepada anggota koperasi berupa pengetahuan  hak dan kewajban  sebagai anggota koperasi serta dasar hukum pengelolaan koperasi,  kemudian dilakukan evaluasi setelah pemberian materi selesai berdasarkan evaluasi. Hasil dari pengabdian ini  ada perbandingan wawasan yang penting pada badan saat sebelum serta setelah pelatihan. Perihal ini cocok dengan terget luaran yang detetapkan berbentuk kenaikan dan pemahaman anggota koperasi terhadap hak dan kewajibannya dan diharapkan dengan berkontribusi terhadap koperasi kredit rukun kota palembang mampu meningkatkan kesejahteraan anggota tersebut berserta keluarganya.